Gagasan Kebangsaan Nadjamoeddin Daeng Malewa Dalam Memajukan Perekonomian Bumiputera Pada Awal Abad 20 di Sulawesi Selatan - St. Junaeda (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to find out Nadjamoeddin Daeng Malewa's ideas related to the development of a people's economy for native people in the Dutch East Indies, especially in South Sulawesi. Apart from having ideas about advancing the economy, Nadjamoeddin has three important ideas about nationality, namely unity, advancing education and advancing the people's economy. This research is historical research that uses historical sources in the form of archives and contemporary newspapers, both those published in Java and those published outside Java such as in Makassar. These sources are cross-checked to obtain valid data, known as source criticism. The results of the research show that the idea of ​​advancing the economy initiated by Nadjamoeddin was carried out by initiating the formation of 54 cooperative villages in Surabaya, forming the Bank Pasar cooperative and becoming chairman of the Minasa Badji cooperative which was founded in Makassar at the end of 1939. All of these things were done by Nadjamoeddin This aims to create a middle class for the native people in the Dutch East Indies.